PENGARUH MODEL PEMBELAJARAN MIND MAP MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP PEMAHAMAN KONSEP BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA NEGERI 1 ANJATAN KABUPATEN INDRAMAYU - Tiharita, Ratna; Anix, Ekayanti Nur (FKIP Unswagati, 2017)
Learning economies rated by students impressed many theories, so it is not easy to understand the material economy. This is caused by the way the students were impressed full text in the economy recorded material resulting in short term memory. Thus, the need for learning model learning Mind Map via audio-visual media that trigger the brain students to think more creatively organized by recording the audio-visual-aided learning media as a learning support so that the benefits can increase students' understanding of the concept and trigger long-term memory. Thus, the formulation of the problem is how the student response, a different perception of the concept of student learning experimental class and control class, and how much influence the learning model learning Mind Map via audio-visual media to the understanding of the concept of student learning?This study aims to determine the students' response to the economic learning by applying learning models Mind Map via instructional media audio-visual equipment, a different perception of the concept of student learning visits than - average value graders control and experiment and its influence applying the learning model Mind Map via instructional media audio-visual to the understanding of the concept of students of class XI IPS.The method used is a quasi-experimental method with a sample of class XI IPS 1 and XI IPS 4 SMAN 1 Anjatan Indramayu. Retrieving data using tests and questionnaires. Tests to measure students' understanding of the concept and a questionnaire to know the student's response. The results showed a good response to the economic learning by applying the learning model of learning Mind Map via audio-visual media of 85.83% and a significant effect on students' understanding of the concept on economic subjects regional international trade material by simple regression test with the results taccount > ttabel is 7314 > 1.701. It meant Ha was accepted and Ho was rejected.Â Keywords: Learning Model of the Mind Map, Learning Media Audio Visual and Concept Training Student Learning.